1935
DOI: 10.1042/bj0290005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the reversible inactivation of papain and cathepsin

Abstract: THE natural activation of cathepsin and papain by sulphydryl compounds acquired increased physiological interest when it became known [Purr, 1933] that the combination, vitamin C-Fe", can activate not only arginase but also cathepsin. Later, Maschmann and Helmert [1934] found a similar activation of papain by the vitamin C-Fe" complex.The activation of these two proteinases by such widely dissimilar types of compounds made it of interest to investigate further the mechanism of these activations. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1937
1937
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The mechanism by which this occurs is not known, but warrants further investigation. It has been reported that iodoacetamide does not cause destruction of the enzyme and that following precipitation of iodoacetamide-inactivated papain with alcohol, the activity may be restored almost to its original level with cysteine (8).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which this occurs is not known, but warrants further investigation. It has been reported that iodoacetamide does not cause destruction of the enzyme and that following precipitation of iodoacetamide-inactivated papain with alcohol, the activity may be restored almost to its original level with cysteine (8).…”
Section: Discussionmentioning
confidence: 99%
“…Cryogel discs (∼0.8 g in weight) were incubated with 0.25 mg·mL –1 papain solution in 0.05 mol·L –1 Tris-HCl buffer (pH 7.5) with 1 mmol·L –1 of EDTA-Na 2 and 5 mmol·L –1 of l -cystein as activators. The activity of the enzyme was determined by spectrophotometry, using BAPNA as a chromogenic substrate . The activity was held constant throughout the degradation period (22.6 ± 1.9 U·g –1 at 25 °C) by adding the required amount of fresh enzyme and a portion of freshly prepared buffer with activators each 24 h. Each time before the fresh enzyme was added, the sample was thrice washed by gentle shaking with an at least 20-times excess of deionized water.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Incubation was carried out with gentle shaking (100 rpm) at 37 °C. The degradation was quenched by intensively rinsing the samples with excess of water and adding 20 mL of 1 mmol·L –1 iodoacetic acid solution in water …”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations